A Pragamatic Approach for Real Time Face Tracking - S., Ranganatha; Gowda M. T., Thirthe; S., Shivashankara; P., Ravi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Live detection and tracking of face(s) is a challenging task in the field of video processing. This paper proposes the detection and live tracking of a single or multiple faces using live video sequences from a webcam with few technical challenges such as partial occlusion, different light intensity levels, and when camera faces different angles. In today’s reality, video analysis is an important task that can help in difficult times. Real time face detection and tracking is one such part of video analysis which is tremendously in use. Today’s productive cameras and high efficiency computers have made the researchers to develop better algorithms for processing the video sequences. Every now and then, system vision and the things we can achieve using this is spoken for versatility in the field of computer vision. Proposed algorithm detect and track the faces very efficiently even when there are constraints from external factors.